Pengaruh Penambahan Pelepah Rebung Bambu (Gigantochloa nigrociliata BUSE-KURZ) dan Konsentrasi Aktivator Terhadap Kualitas Kompos yang Dihasilkan - Daniel Rama Prawiratama; I Wayan Widia; I Nyoman Sucipta (Program Studi Teknik Pertanian, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2020)
The purpose of this study was to obtain the composition of the ingredients and coordinate the optimal activator on compost quality in accordance with the Indonesian National Standard (SNI) 19-7030-2004. The raw materials used in composting are bamboo shoots and cow dung waste. The activator used was from a 2-week fermentation process from a banana hump that was added to rice washing water and brown sugar. The composting process in this study used a bamboo basket with a height of 100cm and a diameter of 60cm. The method used is factorial Completely Randomized Design with two factors. The first factor is the composition of cow dung and tabah bamboo shoot waste which consists of 5 levels, namely: 100%: 0%, 75%: 25%, 50%: 50%, 25%: 75%, and 0%: 100%. The second factor is the concentration of activator consisting of 3 levels, namely 250 ml, 500 ml and 750 ml. Each time repeated 2 times. In the process of composting temperature and pH every day for 31 days. Water content, C-Organic (%), Nitrogen (%) seen at the beginning and end of the composting process. The best combination of A3.B3 treatment with the composition of cow dung and bamboo shoot midrib (50%: 50%) activator concentration of 750 ml, resulted in a peak temperature of 47.250C with an average temperature during the composting process of 40.320C, average pH during composting process 7, 10, final pH 6.93, moisture content 35.95%, organic C content 23.9%, total N-content 1.46%, C / N ratio 16.42%. The resulting compost is blackish brown in color, has a crumb texture compared to other processing. Keywords : tabah bamboo shoots, cow dung, composting, compost quality.